Designing biomass supply chains within planetary boundaries. Issue 4 (20th January 2021) - Wheeler, Jonathan; Galán‐Martín, Ángel; Mele, Fernando D.; Guillén‐Gosálbez, Gonzalo
Abstract: The design of sustainable supply chains, which recently emerged as an active area of research in process systems engineering, is vital to ensure sustainable development. Despite past and ongoing efforts, the available methods often overlook impacts beyond climate change or incorporate them via standard life cycle assessment metrics that are hard to interpret from an absolute sustainability viewpoint. We here address the design of biomass supply chains considering critical ecological limits of the Earth—planetary boundaries—which should never be surpassed by anthropogenic activities. Our method relies on a mixed‐integer linear program that incorporates a planetary boundaries‐based damage model to quantify absolute sustainability precisely. We apply this approach to the sugarcane‐to‐ethanol industry in Argentina, identifying the optimal combination of technologies and network layout that minimize the impact on these ecological boundaries. Our framework can find applications in a wide range of supply chain problems related to chemicals and fuels production, energy systems, and agriculture planning.